2011
DOI: 10.3109/17483107.2011.635330
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a new designed forearm orthosis in treatment of lateral epicondylitis

Abstract: The new-designed orthosis can significantly relieve pain, improve function, increase pain threshold and grip strength after application. This orthosis seemed to be more effective than counterforce orthosis in relieving pain and increasing the pain threshold probably due to the limitation of forearm supination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…18,[167][168][169][170][172][173][174][175][176][177][178][179][180][181][182][183][184][185][188][189][190][191][192][193][194][195][196][197][198] The majority of studies had small sample sizes (≤ 50 participants, n = 18; 51-100 participants, n = 15; > 100 participants, n = 3).…”
Section: Randomised Controlled Trials Not Included In An Existing Sysmentioning
confidence: 99%
“…18,[167][168][169][170][172][173][174][175][176][177][178][179][180][181][182][183][184][185][188][189][190][191][192][193][194][195][196][197][198] The majority of studies had small sample sizes (≤ 50 participants, n = 18; 51-100 participants, n = 15; > 100 participants, n = 3).…”
Section: Randomised Controlled Trials Not Included In An Existing Sysmentioning
confidence: 99%
“…Of them, 26 were selected as study samples who aged 30-55 years [7] and reported pain in the lateral epicondyle of the humerus which aggravated by pressure on the epicondyle and was resistant to wrist extension. The exclusion criteria consisted of receiving any treatment for the condition in the past month; having a history of fracture, dislocation, half dislocation, osteoarthritis or elbow surgery [8]; limited elbow mobility, or suffering from arthritic diseases [5].…”
Section: Methodsmentioning
confidence: 99%
“…Its prevalence in the general population, in jobs requiring repetitive tasks, and in tennis players are 3-8%, 15% and 50%, respectively. It is common in people aged 35-55 years; it is almost twice as frequent in the dominant hand, compared to the non-dominant hand [3][4][5]. LE is one of the most common causes of lateral elbow pain.…”
Section: Introductionmentioning
confidence: 99%
“…After screening based on title and abstract, 79 studies were selected for full-text evaluation. Finally, 17 RCTs 3, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] were considered in the final synthesis. However, one study 3 was removed from the meta-analysis due to categorical data.…”
Section: Study Selectionmentioning
confidence: 99%